TRAINING ON THE UTILIZATION OF IOT SYSTEMS BASED ON BLENDED LEARNING IN SCHOOLS - Munandar; Lidiana; Riyan Maulana (CV. Naskah Aceh, 2022)
In this modern era, technological developments have certainly shown extraordinary progress. Humans are also required to continue to develop and improve their abilities and quality, to be able to master technology and communications that are developing internationally, so that they are able to face increasingly fierce global competition. To create superior, intelligent and quality humans, this can be produced through providing quality education. Therefore, in this case teachers have very important duties, functions, roles and positions, because quality education comes from qualified, qualified, experienced and professional teachers. That is why teachers must always develop and improve their abilities in order to become professional educators. Teachers need to have professional standards by mastering the material and learning models that can encourage their students to want to learn. Professional teachers must have good teaching skills, have broad insight, master the curriculum, master learning models, master technology, always be up to date, have a good personality and be a good role model. Talking about learning models, it is time for us to reinvent learning models that are appropriate to current developments in order to be able to create people who are superior, intelligent, qualified, experienced and not outdated. One of the newest educational issues in the current development of globalization and technology is the Blended Learning learning model which combines face-to-face learning and online learning. Therefore, Blended Learning is a learning model that can be used and utilized to realize the demands of the current digital era of education. And to develop and improve the professionalism of educators in the era of industrial revolution 4.0, the blended learning model is one way to develop and improve the professionalism of educators in accordance with current conditions.